On the Seal Impressions on Some Old Babylonian Tablets - Buchanan, В.
1. Some Old Babylonian Sealings; the Last Has “Kassite” Features — 2. A Syrian and Two Old Babylonian Seals on a Envelope Dated to the Reign of Samsuditana.